The Influence of the Accounting Information System for Providing Credit on Internal Control of Providing Credit: Study at One of The PT. BPR Kerta Raharja Offices in Bandung - Amalia Erfiana Tiara Putri; Siti Mialasmaya; Roro Endah Kumalasari; Galih Putra Prawiranegara (Majalah Bisnis & IPTEK, 2024)
The research was carried out at the Bandung office of PT. BPR Kerta Raharja employed a quantitative methodology, specifically utilizing a descriptive approach and verification methods such as correlation coefficient, simple regression, and coefficient of determination. The sample size in this study consisted of 10 individuals. The research findings indicate that the Accounting Information System for Providing Credit falls under the category of reasonably excellent, with a score of 3.29. Similarly, the Internal Control for Providing Credit is also classified as quite good, achieving a score of 2.96. The calculation of the independent variable, the Accounting Information System for Providing Credit, and the dependent variable, Internal Control of Providing Credit, yielded a correlation value of r = 0.872. The simple linear regression equation is Y = 19.229 + 0.929X. The coefficient of determination (R2), expressed as a percentage, indicates the magnitude of the relationship. The credit-granting accounting information system (X) has a significant influence of 0.872 or 76.1% on credit-granting internal control (Y). The remaining 23.9% is attributed to other factors not examined in this research.